Characterization and Photocatalytic Evaluation (UV-Visible) of Fe-doped TiO2 Systems Calcined at Different Temperatures (2015)
ABSTRACT: There is growing interest in obtaining compounds with photocatalytic activity in the solar spectrum, and this has led to intense research on the topic. In our laboratory, Fe-doped TiO2 was synthesized using the sol-gel method combined with the solvothermal technique at 200°C and calcined at temperatures between 350oC and 620oC. The samples were characterized by X-ray diffraction, Micro-Raman spectroscopy, Brunauer-Emmett-Teller specific surface area, diffuse reflectance spectroscopy, X-ray fluorescence and photocatalytic activity. All materials crystallized in the anatase phase. Additionally the 0.05% Fe-doped TiO2 calcined at 620°C showed the presence of the rutile phase while 0.1% Fe-doped TiO2 calcined at 620°C showed the presence of the brookite phase. Photoactivity was observed in the visible spectrum for 0.05% and 0.1% Fe-doped TiO2, calcined at 620oC. Visible activity was attributed to the presence of rutile and an absorption shift to the visible spectrum. Because of the temperature increment, the crystal size grew and the surface area decreased.